Relationship between Commercial Banks Credit and Per capita net state domestic product of India: A Regional Panel data analysis - Datta, Kanchan (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
In general, bank credit plays a pivotal role in economic growth. Because bank credit may stimulate the capital accumulation and rate of saving that further induce the economic growth. However there are no unanimous opinion on the relationship between bank credit and economic growth. Under these circumstances, an attempt has been taken in this paper to investigate the role of bank credit, capital outlay and government’s social sector spending on per capita net state domestic product of India . this study finds that random effect model is better than fixed effect model and expansion of bank credit significantly affecting the per capita net state domestic product, capital outlay also positively and significantly affecting the per capita net state domestic product